Assessment of Knowledge, Attitude, and Practice of Sunlight Exposure of Infants among Mothers Attending in Governmental Health Facilities in Farta District, South Gondar Zone, North West Ethiopia, 2018. (23rd September 2019) - Gedamu, Haileyesus; Tafere, Yilkal
Abstract : Background . Sunlight exposure serves an important purpose in human bodies. It promotes good health and plays a major role in the production of the very essential vitamin, vitamin D. Vitamin D is important for the growth of healthy, normal bones. Research conducted in different areas suggested that daily exposure to sunshine remains the cheapest, safest, and most effective method of preventing rickets. Objective. To assess knowledge, attitude, and practice of infants to sunlight exposure among lactating women in Farta district, in 2018. Method. Institution based cross sectional study design was conducted among mothers attending the selected health center. Systematic sampling method was used to select individual respondents. Data were entered and analyzed by using SPSS version 20. Result. Among 357 respondents identified for the study, 95% (n = 339 ) was responding to the interview. Of the total respondents, 49.9%, 46%, and 45.7% of them had poor knowledge, unfavorable attitude, and poor practice about sunlight exposure, respectively. Conclusion and recommendation. The results of this study showed that almost half of the mothers had inadequate knowledge, attitude, and inadequate practice about sunlight exposure. Therefore, mothers need to be educated about the importance of sunlight exposure.